The Effect of Restoration Treatments on the Regeneration Pathway in Alpine Seed Plants - Hoff, Ellen Torsæter (Institutt for biologi, 2011)
Question: How does nutrient addition and seeding affect revegetation of seed plants, and are the effects differing among the stages of the regeneration pathway? Location: Two roads restored in 2002, located in Hjerkinn firing range, in lower alpine zone of Dovrefjell, Norway.Methods: Abundance of species and functional types (dwarf shrubs, forbs and graminoids) in four stages of the regeneration pathway (seed rain, seed bank, field seedlings and established vegetation) was recorded seven years after road reconstruction in treatment plots (with nutrient addition, nutrient + seed addition and no treatment). Results: The graminoid Deschampsia cespitosa dominated the vegetation and seed rain in fertilized plots, while the seeded Festuca rubra still dominated the seeded + fertilized plots. The germinable seed bank was lowest in the seeded + fertilized treatment, while the control plots had the highest number of seedlings germinating in the field. Dwarf shrubs had a high germination rate in the field, despite low rates in the seed rain and seed bank. The highest rate of dwarf shrub seedlings was in control plots, while the frequency of dwarf shrubs in the established vegetation increased with nutrient addition. Forbs had species specific responses.Conclusions: Both treatments that included nutrients were dominated by graminoids, with a higher vegetation cover and frequency of dwarf shrubs than the control plots. While graminoids are the most efficient seed producers, they are less able to germinate and survive as seedlings. Dwarf shrubs accounted for a high proportion of germinating seedlings in the field, but the low frequencies of dwarf shrubs in the established control plot vegetation suggest either low seedling survival or an ongoing successional change. It remains to be revealed if the high recruitment of dwarf shrubs in the control plots will speed up the establishment of the typical dwarf shrub cover similar to the surrounding vegetation and hereby indicate that unassisted recovery is the fastest way to restore ...